Pedosedimentary environments in the Caspian Lowland during MIS5 (Srednaya Akhtuba reference section, Russia). (20th July 2021) - Makeev, Alexander; Lebedeva, Marina; Kaganova, Alexandra; Rusakov, Alexey; Kust, Pavel; Romanis, Tatiana; Yanina, Tamara; Kurbanov, Redzhep
Abstract: Srednaya Akhtuba outcrop provides a detailed record of the Late Pleistocene continental and marine deposits and paleosols from MIS5 to MIS1. The MIS5 chronozone is presented by a continuous pedosedimentary sequence with three well-developed paleosols. The paper is based on the study of depositional environment and pedostratigraphy, with OSL chronological framework and precise altitude references. Field data are supported by chemical analyses, micromorphology, and clay mineralogy. A detailed study of MIS5 paleosols was first conducted for the Lower Volga area. Pedosedimentary sequence at that time developed on the river terrace in a backswamp and/or wetland influenced by extremely slow-moving stream after long seasonal floods. Thin loess layers were deposited during the brief episodes of low flood activity, while fluvial heavy loams – at the time of more intensive flooding. Mollic Gleysols and Fluvic Chernozems have been formed in the arid or semi-arid climate with seasonal freezing under productive wet meadows. Changes in the depositional environment resulted in the formation of welded paleosols, marked by textural difference, cryogenic levels, and accretionary humus horizons. Despite the complicated depositional pattern and the influence of seasonal floods, the MIS5 pedosedimentary sequence may serve as a good stratigraphic marker for the onset of Late Pleistocene allowing correlation with loess-paleosol sequences of the whole Ponto-Caspian region and linking it with the global stratigraphic schemes.